Предмет: Алгебра,
автор: marikamarika2
5(x+3)^2-5(x-4)(x+8)+12=87
Ответы
Автор ответа:
0
5( х + 3 )^2 - 5( х - 4)( х + 8 ) + 12 = 87
5( х^2 + 6х + 9 ) - 5 ( х^2 + 8х - 4х - 32 ) = 87 - 12
5( х^2 + 6х + 9 - х^2 - 4х + 32 ) = 5•15
10х + 41 = 15
х = - 26 : 10
х = - 2,6
5( х^2 + 6х + 9 ) - 5 ( х^2 + 8х - 4х - 32 ) = 87 - 12
5( х^2 + 6х + 9 - х^2 - 4х + 32 ) = 5•15
10х + 41 = 15
х = - 26 : 10
х = - 2,6
Похожие вопросы
Предмет: Английский язык,
автор: madi7457
Предмет: Қазақ тiлi,
автор: kolerting
Предмет: Алгебра,
автор: mebelsiti17
Предмет: Биология,
автор: cobakav